Analisis Wacana Kritis Model Teun A. Van Dijk “Siswa Berprestasi Jadi Pembunuh” - Nurul Musyafa'ah (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2017)
Discourse analysis is a study that examines or analyzes the language used by nature, both in written and spoken from. By analysis a discourse, easily we known the ideology that is hidden behind the text of a news. In this discourse analysis will reveal some questions 1. How the process of critical analysis discourse from a news? 2. How does the context of news discourse of criminality “Student Achievement be a killer” in theory Van Dijk? This study is qualitative descriptive research with basic research using the method of critical discourse analysis Teun Van Dijk. Descriptive data are collected in the form words, images, and not numbers. Therefore the research report will contained the data to illustrated the presentation of the report. The result of this discussion is by using discourse analysis is able to maintain security and orderliness country so that not easily provoked by a news before further analyze the purpose of such report and compare it to the news published by other media, in this problem can conclude that the news that published by kompas is trying to accentuate the perpetrator by giving describe in each of what is there have a connection with him.